2023
DOI: 10.3389/fevo.2023.1289433
|View full text |Cite
|
Sign up to set email alerts
|

A chimpanzee’s time to feast: seasonality of Macrotermes flight hole activity and alate dispersal flights detected by termite-fishing experiments and camera traps in the Issa Valley, Tanzania

Seth Phillips,
Alex K. Piel,
Fiona A. Stewart
et al.

Abstract: IntroductionInvestigation into chimpanzee termite-fishing behavior has provided invaluable insights into the evolution of animal tool use and culture. However, research to date often overlooks how the ecology of termites may shape the nature of this predator–prey interaction. Though anecdotal links between meteorological factors, termite dispersal flights and the ability of chimpanzees to termite-fish have been made, these relationships were never empirically tested. In this study, we examined if and how the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Our study focused on whether seasonal termite fishing by Nigeria‐Cameroon chimpanzees ( P. t. ellioti ) in central Cameroon was consistent with the “necessity” and/or “opportunity” hypotheses for tool‐use behavior. Our findings revealed a relationship between rainfall, termite accessibility, and termite consumption by chimpanzees that is consistent with the “opportunity hypothesis” and with recent findings from a chimpanzee community in east Africa (Phillips et al., 2023 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study focused on whether seasonal termite fishing by Nigeria‐Cameroon chimpanzees ( P. t. ellioti ) in central Cameroon was consistent with the “necessity” and/or “opportunity” hypotheses for tool‐use behavior. Our findings revealed a relationship between rainfall, termite accessibility, and termite consumption by chimpanzees that is consistent with the “opportunity hypothesis” and with recent findings from a chimpanzee community in east Africa (Phillips et al., 2023 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous work examining seasonal termite reproductive behavior for mound‐building termites suggests they cue mating flights based on environmental signals. Mating flights for Macrotermes species, a well‐known target of chimpanzee termite fishing, have been shown to be triggered by rainfall, which aligns with the findings of this study (Mitchell, 2008 ; Phillips et al., 2023 ). Other research has also identified temperature, wind speed, and humidity as important factors determining the timing of termite reproductive behavior (Mitchell, 2008 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations